Penggunaan Media Pembelajaran Matematika Berbasis E-Learning Untuk Meningkatkan Motivasi dan Hasil Belajar Mahasiswa - Wahyuni, Arie; Hidayati, Destia Wahyu (Politeknik Indonusa Surakarta, 2023)
The development of information technology is now growing and important, so that in the world of education it will always be used. One of the information technologies used in the world of education is e-learning. This study aims to use e-learning-based mathematics learning media to increase student motivation and learning outcomes. Pre experimental design with one-group pretest posttest design is a type of this research. The method used in this research is descriptive method. The research instruments included validation sheets for learning mathematics media (media experts and material experts), student questionnaires and student learning outcomes. The results of the validation of the mathematics learning media obtained by the material expert on average were 3.75 (interesting), and the media expert obtained an average of 4.6 (very interesting). From these results states that the mathematics learning media is feasible to use. The results of the student’s motivation response using e-learning-based mathematics learning media were very strong, namely 75% agree, 20% strongly agree, disagree and strongly disagree 5% and 0%, respectively. The average student learning outcomes after using e-learning-based mathematics learning media increased, namely the average pre-test results were 43.90 and the average post-test results were 78.30.